Effect of Cooling Rate on Microstructure and Mechanical Properties According to Heat Treatment Temperature of Inconel 625 - Minha Park; Gang Ho Lee; Hyo-Seong Kim; Byoungkoo Kim; Sanghoon Noh; Byung Jun Kim (Archives of Metallurgy and Materials)
Inconel 625 is typically used in extreme environments due to excellent mechanical properties such as high strength, corrosion resistance, abrasion resistance and low-temperature toughness. When manufacturing a hot forged flange with a thick and complex shape, the cooling rate varies depending on the location due to the difference in thermal gradient during the cooling process after hot forging. In this study, to evaluate the microstructure and mechanical properties of Inconel 625 according to the cooling rate, we performed heat treatment at 950°C, 1050°C, and 1150°C for 4 hours followed by water cooling. Additionally, temperature data for each location on the flange were obtained using finite element method (FEM) simulation for each heat treatment temperature, revealing a discrepancy in the cooling rate between the surface and the center. Therefore, the correlation between microstructure and mechanical properties according to cooling rate was investigated.